The clinical characteristics of patients with sepsis in a tertiary referral hospital in Yangon, Myanmar. (9th November 2018) - Ye Lynn, Kyi Lai; Hanson, Josh; Mon, Nan Cho Nwe; Yin, Kyi Nyein; Nyein, Myo Lwin; Thant, Kyaw Zin; Kyi, Mar Mar; Oo, Thin Zar Cho; Aung, Ne Myo
Abstract: Background: The clinical characteristics and course of patients hospitalised with sepsis in Myanmar and the responsible pathogens remain poorly defined. Methods: We performed an observational study of adults admitted from the community to a tertiary referral hospital in Yangon with fever and dysfunction of at least two organ systems. Results: The 120 patients had a median age of 47 y (interquartile range 28–63); 11 (9%) were human immunodeficiency virus positive. Limited laboratory support meant that a microbiological diagnosis was possible in only 35 (29%) patients, but 18 (13%) had pathogens in blood cultures, including 9 (50%) organisms that were multidrug resistant (4 Escherichia coli, 4 Pseudomonas aeruginosa, 1 Burkholderia pseudomallei ). Tuberculosis was confirmed in six patients, with two being rifampicin resistant, and dengue infection was confirmed in five patients. Without access to comprehensive intensive care support, 34 (28%) patients died. An admission National Early Warning Score ≥7 (odds ratio [OR] 8.6 [95% confidence interval CI 2.6 to 28.2], p=0.001) and quick sequential (sepsis-related) organ failure assessment score ≥2 (OR 3.2 [95% CI 1.3 to 8.0], p=0.02) were helpful in predicting death. Conclusions: Tropical pathogens are a common cause of sepsis in Myanmar. The frequent identification of multidrug-resistant organisms and limited diagnostic and intensive care support hinder patient care significantly. However, simple clinical assessment on admission has prognostic utility.